Minat Individu Terhadap Penggunaan Internet Banking: Pendekatan Modified Technology Acceptance Model .(Studi Kasus pada Nasabah Bank BCA di Surakarta) - Aryani, Muftafifa Higya, Dr. Triyono, SE, M.Si (2016)
This study purposes to examine the factors that influence intention to use internet banking services by modified a model of Technology Acceptance Model (TAM) developed by Davis in1989. Used in this study population was all the customers Bank BCA in Surakarta. The data used in this research is primary data and data collection was performed using a questionnaire. A method of the sample collection by way of a method of convenience. The total sample collected as many as 60 customers and the questionnaires back and the questionnaire can be processed as many as 60. Analysis technique in this study was multiple linear regression analysis. The result of analysis for this model shows that the construct perceived usefulness, trust and perceived risk affect the intention to use internet banking. Even though that perceived ease of use and security did not influence the intention to use internet banking. This means that the intention to use internet banking is influenced by the perceived usefulness, trust and perceived risk.